2018
DOI: 10.1055/a-0594-2373
|View full text |Cite
|
Sign up to set email alerts
|

Welche Faktoren sind mit Verhaltensauffälligkeiten im Vorschulalter assoziiert? Eine Sekundärdatenanalyse der Schuleingangsuntersuchungen von 2010 bis 2014 in der Region Hannover

Abstract: The results point to the importance of early development support for children from socially disadvantaged families. The results highlight public health-relevant points and enable the region Hannover to improve preventive efforts targeting such pre-school children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Many previous studies have focused on psychological and behavioural problems among children in low-income and high-income families. 31,32 These studies showed that children in low-income families had more implicit and explicit problems as well as weak social abilities. 33 Related interventional studies also revealed that helping poor families increase their income significantly improved the psychological problems in these children's families.…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies have focused on psychological and behavioural problems among children in low-income and high-income families. 31,32 These studies showed that children in low-income families had more implicit and explicit problems as well as weak social abilities. 33 Related interventional studies also revealed that helping poor families increase their income significantly improved the psychological problems in these children's families.…”
Section: Discussionmentioning
confidence: 99%
“…The results of school entry health examination at the federal-state level, for example, demonstrate socioeconomic differences in the prevalence of psychological problems. They show that socioeconomically disadvantaged children are more likely to face mental health problems than those from families with a higher SES [ 21 , 50 ]. The WHO-funded Health Behaviour in School-aged Children (HBSC) study demonstrates that social inequalities in the health and well-being of the young generation are also found in other industrialised nations – usually with detrimental impact for children and adolescents from socioeconomically disadvantaged families [ 51 ].…”
Section: Discussionmentioning
confidence: 99%